Outer membrane vesicles produced by Burkholderia cepacia cultured with subinhibitory concentrations of ceftazidime enhance pro-inflammatory responses. Issue 1 (1st January 2020) - Kim, Se Yeon; Kim, Mi Hyun; Son, Joo Hee; Kim, Seung Il; Yun, Sung Ho; Kim, Kyeongmin; Kim, Shukho; Shin, Minsang; Lee, Je Chul
ABSTRACT: Burkholderia cepacia: is an opportunistic pathogen that infects patients with debilitating underlying diseases. This study investigated the production of outer membrane vesicles (OMVs) by B. cepacia cultured with sub-minimum inhibitory concentrations (MICs) of antibiotics and examined their pathogenic roles both in vitro and in vivo. B. cepacia ATCC 25416 produced more OMVs under antibiotic stress conditions than controls. OMVs isolated from B. cepacia cultured in Luria-Bertani (LB) broth (OMVs/LB) induced cytotoxicity and the expression of pro-inflammatory cytokine genes in A549 cells in a dose-dependent manner. Host cell cytotoxicity and pro-inflammatory responses were significantly higher in A549 cells treated with B. cepacia OMVs cultured with 1/4 MIC of ceftazidime (OMVs/CAZ) than in the cells treated with OMVs/LB, OMVs cultured with 1/4 MIC of trimethoprim/sulfamethoxazole (OMVs/SXT), or OMVs cultured with 1/4 MIC of meropenem. Intratracheal injection of B. cepacia OMVs also induced histopathology in vivo in mouse lungs. Expressions of IL-1β and TNF-α genes were significantly up-regulatedin the lungs of mice treated with OMVs/CAZ compared to mice administered other OMVs; the expression of the GRO-α gene, however, was significantly up-regulated in OMVs/SXT. In conclusion, OMVs produced by B. cepacia under different antibiotic stress conditions induce different host responses that may contribute to the pathogenesis of B. cepacia .